A Study of Online Platforms Learning During the Covid-19 Pandemic in College - Syahraini Ritonga; Witma Novita Atnur; Erlia Utami Panjaitan; Defri Rahmat; Rahmi Syafriyeti (Universitas Pahlawan Tuanku Tambusai, 2022)
Nearly a billion individuals have been quarantined since the COVID-19 epidemic began. As a result, several nations, including Indonesia, have enacted legislation prohibiting all forms of schooling and requiring governments and allied agencies to develop alternate ways of instruction for each educational institution. On the other hand, universities that have not yet developed an infrastructure for online learning may encounter obstacles. Many professors and students are wary of implementing online learning methodologies due to the ingrained culture of the traditional educational system. The study's objective was to ascertain how teaching and learning activities were conducted a year after Al Washliyah Labuhanbatu University was closed due to an epidemic. The study employed a mixed-method approach, collecting quantitative and qualitative data using questionnaires. The mixed-method strategy was supplemented with a Google Forms-based online questionnaire distributed to 100 students. Over 75% of instructors include video conferencing, learning management systems, and instant messaging in their presentations. During Covid-19 at Al Washliyah University, teachers agreed that combining the three platforms reduced obstacles to online learning and increased lecturers' and students' familiarity with the usage of online learning materials.